Learning Outcomes of Psychomotor Domains in Welding Technology: VR Welding Kit Assessment: A Systematic Literature Review - Arifin, Ardian; Seth, Nur Hazirah Noh; Zainuddin, Norziha Megat Mohd.; Norehan Haron, Habibah (Journal of Education Culture and Society, 2024)
Aim. This systematic literature review aims to analyse existing studies that have investigated the impact of VR welding kits on the development of psychomotor skills, knowledge acquisition, and overall learning experience. By synthesising findings from a variety of sources, this review seeks to provide insight into the strengths, limitations, and potential areas for further research in this domain. Method. This systematic literature review involved an extensive search of electronic databases such as PubMed, Google Scholar, and IEEE Xplore to identify relevant studies that focused on the impact of VR welding kits on psychomotor skills development and knowledge acquisition. Result. Findings from a systematic literature review reveal a range of results related to the impact of VR welding kits on psychomotor skills development and knowledge acquisition. Most of the research highlights the positive effects of utilising VR technology in welding education. VR welding kits were invented to improve learners’ psychomotor skills by providing a realistic and interactive simulation environment. Conclusion. Ongoing research in this domain will be critical to refining and integrating VR welding technology into welding education and practice, ultimately positioning the industry for a future that improves productivity, safety, and competitiveness. Cognitive Value. Allowing students to practice and refine welding techniques in a safe and controlled setting, ultimately leading to increased proficiency and confidence in practical applications. The insights gained from this review have significant implications for educators, training programs, and the welding industry.